2023
DOI: 10.3389/feart.2022.1122579
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a borehole stress meter in rocks surrounding the roadway, based on optical-fiber sensing technology

Abstract: Stress in rock masses is an important parameter in the design and construction of underground engineering, such as the design and maintenance of mine roadways and the design of mining working faces. It is also a fundamental force causing the deformation and failure of geotechnical engineering excavation. At present, the abutment-pressure monitoring technology of the surrounding rocks of the coal mine roadway in China is not intelligent and systematic and lacks some high-precision sensing instruments and multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The focus of this discussion is mainly on strain, humidity, and temperature measurements-all of which are critical to geotechnical applications [27,[39][40][41][42][43]. However, OF sensors are employed in various other applications including electrical fields and chemical sensors for which comprehensive reviews may be found in the literature [44][45][46][47][48].…”
Section: Types Of Fibre-optic Sensorsmentioning
confidence: 99%
“…The focus of this discussion is mainly on strain, humidity, and temperature measurements-all of which are critical to geotechnical applications [27,[39][40][41][42][43]. However, OF sensors are employed in various other applications including electrical fields and chemical sensors for which comprehensive reviews may be found in the literature [44][45][46][47][48].…”
Section: Types Of Fibre-optic Sensorsmentioning
confidence: 99%